The predictive value of triglyceride-glucose index on early neurological functional improvement in non-diabetic patients with acute ischemic stroke undergoing intravenous thrombolysis - Li, Furong; Sui, Xiaowen; Pan, Xin; Li, Jun; Gao, Yan; Shi, Dandan; Zhao, Hongling; Chen, Dong (Frontiers in Neurology, 2025)
ObjectiveTo explore the predictive role of the triglyceride-glucose index (TyG index) on the early neurological improvement in non-diabetic patients with acute ischemic stroke (AIS) undergoing alteplase intravenous thrombolysis (IV-rtPA).MethodsThis study included 490 AIS patients without diabetes, whose time from onset to hospital time ≤3 h undergoing IV-rtPA in the Stroke Center of our hospital from September 2023 to September 2024 through the Stroke Emergency Map Management Platform in Dalian City. According to the National Institutes of Health Stroke Scale (NIHSS) score at 24 h after IVT, the patients were divided into early neurological improvement (ENI) group (n = 332) and non-ENI group (n = 158). General information, risk factors, experimental data and the location of cerebral infarction were collected. Intergroup analyses were conducted using univariate or multivariate logistic regression.Results(1) In the ENI group, blood glucose (FBG), triglycerides (TG), TyG index, and baseline NIHSS score were significantly lower than those in the non-ENI group (p < 0.05). (2) Binary logistic regression analysis indicated that a TyG index ≤7.15 and a low baseline NIHSS score could predict early neurological improvement undergoing intravenous thrombolysis (IVT) in AIS patients. The area under the curve (AUC) values for the TyG index, baseline NIHSS score, and the combined variable (Y) in predicting ENI were 0.640, 0.641, and 0.721, respectively, with the combined variable (Y) exhibiting the highest AUC value.ConclusionThe TyG index, baseline NIHSS score, and the combined variable (Y) are predictors of early neurological improvement, with the combined variable (Y) exhibiting a higher predictive efficiency.